Analisis Kinerja Keuangan Perusahaan Pada Sektor Infrastruktur Yang Terdaftar Di BEI Sebelum Dan Pada Saat Pandemi COVID-19 - Abel Sonia S; Rizky Raditya Pratama; Fitri Yani Panggabean (Jurnal Ekonomi dan Bisnis Digital, 2025)
This study aims to analyse the financial performance of infrastructure sector companies listed on the Indonesia Stock Exchange (IDX) before and during the COVID-19 pandemic. The COVID-19 pandemic that has hit since early 2020 has had a significant impact on economic activity, including the infrastructure sector which is highly dependent on mobility and long-term investment. Performance analysis is carried out by comparing key financial ratios such as profitability (ROA, ROE, NPM), liquidity (CR, QR), solvency (DER), and activity (TATO) in the period 2018-2019 (before the pandemic) and 2020-2021 (during the pandemic). The analysis method used in this research is descriptive quantitative analysis with a comparative approach. The results showed that in general, there was a decline in the financial performance of most infrastructure sector companies during the pandemic, especially in the aspects of profitability and activity. This decline reflects operational disruptions and decreased demand due to social restrictions and economic uncertainty. However, some companies have managed to maintain stable performance thanks to business diversification and operational efficiency. These findings provide important insights for investors and company management in anticipating financial risks in times of crisis.